KEMAMPUAN LITERASI MATEMATIS MAHASISWA CALON GURU SEKOLAH DASAR - Desy Dwi Riana; Zenizela, Zeidenes (Universitas Islam Balitar, 2020)
The purpose of this research was to describe the level of mathematics literacy of Primary School teacher candidates. This research was carried out in the Faculty of Teacher Training and Education, Primary School Teacher Education Department, Universitas Islam Balitar Blitar by adopting qualitative approach. The subjects of this research were the third semester students of Primary School Teacher Education Department of 2019/2020 academic year. A total of 3 students were selected by using purposive sampling technique. The levels of mathematics literacy were classified into high, moderate, and low levels. Test, interview, and documentation were conducted to obtain the data. Initially, a test was performed to classify the students’ mathematics ability. Then, the three students were given codes: S1 was high ability, S2 was moderate ability, and S3 was low ability. The subjects did a mathematics literacy test, and subsequently followed by interview to strengthen the findings from the test. The results of this research revealed that concerning the level of mathematics literacy, S1 achieved level 5, S2 attained level 3, while S3 still reached level 1. Based on the findings, it can be concluded that the levels of mathematics literacy of Primary School teacher candidates have yet to be optimum.